Color and expressiveness in the construction timbers by means surface treatments with acids - Lora Toro , Francisco; García Santos, Alfonso; Rodríguez Rodríguez, Antonio (Revista de la Construcción. Journal of Construction, 2018)
The aim of this research is to compare the uniformity of the color histograms of the RGB color space between the traditional surface treatment with fire against the controlled surface treatment of colorless acids in liquid state on construction timbers, developed by the authors. A “conceptual translation” is proposed as a starting point, from the processes applied on construction timbers with treatments by means of fire (whose aim is not the color) to controlled surface treatment of colorless acids in liquid state on construction timbers. The color histograms of the RGB color space are compared of both treatments and it is concluded that the controlled surface treatment of colorless acids in liquid state on construction timbers obtains a more uniform distribution of color histograms than the traditional surface treatment with fire.